2014
DOI: 10.1021/jp504306m
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition of Formaldehyde Multilayer Films on Deoxygenated, Oxygenated, and Water-Adsorbed Vanadium Substrates at Cryogenic Temperatures

Abstract: Interactions of thin formaldehyde films with a polycrystalline V substrate were investigated using temperatureprogrammed desorption and time-of-flight secondary ion mass spectrometry. A multilayer formaldehyde film grows on a deoxygenated V substrate at 70 K after the formation of a reacted layer at the interface. Most molecules in the film disappear at 100 K via interfacial reaction rather than thermal desorption. However, the liberation of possible reaction products such as H 2 and CO is depressed at T < 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…The hydrogen abstraction can occur at this stage from the methyl species as well. The dehydrogenation is ineffective from the methylene species; 29,30 it can be incorporated in the subsurface layers without further dissociation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hydrogen abstraction can occur at this stage from the methyl species as well. The dehydrogenation is ineffective from the methylene species; 29,30 it can be incorporated in the subsurface layers without further dissociation.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to molecules in the submonolayer regime, those in multilayer lms are thought to desorb without decomposition because physisorbed molecules are not inuenced by chemical properties of metal substrates. It was recently demonstrated that this conventional picture does not hold for a clean V substrate: most of water, 28 methanol, 29 and formaldehyde 30 molecules in thin lms are decomposed. However, the reaction mechanism of multilayer lms at the interface is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…This behavior is a characteristic of n-hexane decomposition because thermal desorption and decomposition of molecules occur simultaneously for other molecular films, including benzene. [20][21][22][23] The decomposition process of the n-hexane film was examined further using temperature-programmed TOF-SIMS. The intensities of typical cations sputtered from the n-hexane film (formed by exposure of 20 L) are shown in Fig.…”
Section: Decomposition Of N-hexane On Vmentioning
confidence: 99%
“…However, physisorbed molecules in multilayer films generally desorb with no reactions except for those in direct contact with metal substrates. Recently, it was demonstrated that this conventional pattern does not hold for multilayers of water, 20 methanol, 21 formaldehyde, 22 ethanol, 23 acetone, 23 and diethyl ether 23 deposited onto a clean V substrate. It was proposed that the deoxygenation reaction to form oxides in the V substrate induces the decomposition of these molecules.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation